Non-invasive optical neuromonitoring of the temperature-dependence of cerebral oxygen metabolism during deep hypothermic cardiopulmonary bypass in neonatal swine. Issue 1 (January 2020) - Ko, Tiffany S; Mavroudis, Constantine D; Baker, Wesley B; Morano, Vincent C; Mensah-Brown, Kobina; Boorady, Timothy W; Schmidt, Alexander L; Lynch, Jennifer M; Busch, David R; Gentile, Javier; Bratinov, George; Lin, Yuxi; et al.
Management of deep hypothermic (DH) cardiopulmonary bypass (CPB), a critical neuroprotective strategy, currently relies on non-invasive temperature to guide cerebral metabolic suppression during complex cardiac surgery in neonates. Considerable inter-subject variability in temperature response and residual metabolism may contribute to the persisting risk for postoperative neurological injury. To characterize and mitigate this variability, we assess the sufficiency of conventional nasopharyngeal temperature (NPT) guidance, and in the process, validate combined non-invasive frequency-domain diffuse optical spectroscopy (FD-DOS) and diffuse correlation spectroscopy (DCS) for direct measurement of cerebral metabolic rate of oxygen ( CMRO 2 ). During CPB, n  = 8 neonatal swine underwent cooling from normothermia to 18℃, sustained DH perfusion for 40 min, and then rewarming to simulate cardiac surgery. Continuous non-invasive and invasive measurements of intracranial temperature (ICT) and CMRO 2 were acquired. Significant hysteresis ( p  < 0.001) between cooling and rewarming periods in the NPT versus ICT and NPT versus CMRO 2 relationships were found. Resolution of this hysteresis in the ICT versus CMRO 2 relationship identified a crucial insufficiency of conventional NPT guidance. Non-invasive CMRO 2 temperature coefficients with respect to NPT ( Q 10  = 2.0) and ICT ( Q 10  = 2.5) are consistent with previous reports and provide further validation of FD-DOS/DCS CMRO 2 monitoring during DH CPB to optimize management.